2012
DOI: 10.3892/ijo.2012.1391
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular targets regulated by tumor suppressors microRNA-1 and microRNA-133a in bladder cancer

Abstract: Abstract. Our expression signatures of human cancer including bladder cancer (BC) revealed that the expression of microRNA-1 (miR-1) and microRNA-133a (miR-133a) is significantly reduced in cancer cells. In the human genome, miR-1 and miR-133a are located on the same chromosomal region (miR-1-2 and miR133a-1 on 18q11.2, and miR-1-1 and miR-133a-2 on 20q13.33) called cluster. In this study, we identified the novel molecular targets commonly regulated by miR-1 and miR-133a in BC. Genome-wide molecular target sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Similar results were observed with the knockdown of miR-1 targeted gene SRSF9 [58]. In another recent study by the same group, novel molecular targets regulated by miR-1 in bladder cancer were identified [59]. Genome-wide molecular target search and luciferase reporter assays showed that prothymosin- α (PTMA) and PNP are directly regulated by miR-1.…”
Section: Aberrant Expression Of Mir-1 In Human Cancerssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were observed with the knockdown of miR-1 targeted gene SRSF9 [58]. In another recent study by the same group, novel molecular targets regulated by miR-1 in bladder cancer were identified [59]. Genome-wide molecular target search and luciferase reporter assays showed that prothymosin- α (PTMA) and PNP are directly regulated by miR-1.…”
Section: Aberrant Expression Of Mir-1 In Human Cancerssupporting
confidence: 65%
“…PTMA and PNP were identified as new target genes regulated by miR-1 in bladder cancer. These genes may function as oncogenes contributing to cell proliferation and invasion in bladder cancer [59]. PTMA is one of the miR-1 target genes involved in miR-1 inducing apoptosis.…”
Section: Aberrant Expression Of Mir-1 In Human Cancersmentioning
confidence: 99%
“…They also demonstrated that transient transfection of BC cell lines with miR-133a, miR-1, and miR-218, reduced the expression of mRNA and protein levels of LIM and SH3 protein 1 (LASP1), an actin binding protein, and reduced cell viability [30]. This group showed that miR-1 and miR-133a targets the genes encoding transgelin 2 (TAGLN2), a protein with unknown function but an observed clinical correlation with BC tumor grade [31], as well as prothymosin-α (PTMA), which is involved in cellular proliferation and differentiation, and purine nucleoside phosphorylase (PNP), an enzyme that catalyzes phosphorolysis of purine nucleosides and when deficient results in impaired cell-mediated immunity [32]. In addition, they reported that miR-1 may mediate apoptosis through inhibition of splicing factor arginine/serine-rich 9 (SRSF9/SRp30s) [33] and that miR-133a induces apoptosis via regulation of glutathione S-transferase π1 (GSTP1) where transfection of cell lines with miR-133a reduced mRNA and protein expression levels of GSTP1 [27].…”
Section: Resultsmentioning
confidence: 99%
“…There are 2,418 targets predicted for miR-630 by the miRanda algorithm and NSAID upregulation of miR-630 might thus influence on tumor growth (44). Other miRNAs, acting as tumor suppressors and frequently downregulated in human solid cancers, are miR-1, miR-133a, miR-133b and miR-206 (4550). miR-1 and miR-133a form clusters on two chromosomes, at 20q13 and 18q11, producing mature miRs with identical sequences, while miR-206 and miR-133b are located at chromosome 6p12 (51).…”
Section: Discussionmentioning
confidence: 99%